A numerical investigation of non-rotational, rigid spherical particle sedimentation problem in viscous fluid - Phan, Nguyen Hong; Diep, Nguyen Van (Vietnam Journal of Mechanics, 2002)
This paper can be considered as continuous part of [1], where the generalized diffusion theory of rigid spherical particle sedimentation in viscous fluid was investigated. Here a numerical solution of non-stationary sedimentation process is obtained by using the explicit finite difference method. The obtained results show that this model can be used for qualitative study of physical phenomenon of sedimentation problem.